Role for Galectin‐3 in Calcific Aortic Valve Stenosis - J. Rafael Sádaba; Ernesto Martínez‐Martínez; Vanessa Arrieta; Virginia Álvarez; Amaya Fernández‐Celis; Jaime Ibarrola; Amaia Melero; Patrick Rossignol; Victoria Cachofeiro; Natalia López‐Andrés (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2016)
BackgroundAortic stenosis (AS) is a chronic inflammatory disease, and calcification plays an important role in the progression of the disease. Galectin‐3 (Gal‐3) is a proinflammatory molecule involved in vascular osteogenesis in atherosclerosis. Therefore, we hypothesized that Gal‐3 could mediate valve calcification in AS. Methods and ResultsBlood samples and aortic valves (AVs) from 77 patients undergoing AV replacement were analyzed. As controls, noncalcified human AVs were obtained at autopsy (n=11). Gal‐3 was spontaneously expressed in valvular interstitial cells (VICs) from AVs and increased in AS as compared to control AVs. Positive correlations were found between circulating and valvular Gal‐3 levels. Valvular Gal‐3 colocalized with the VICs markers, alpha‐smooth muscle actin and vimentin, and with the osteogenic markers, osteopontin, bone morphogenetic protein 2, runt‐related transcription factor 2, and SRY (sex‐determining region Y)‐box 9. Gal‐3 also colocalized with the inflammatory markers cd68, cd80 and tumor necrosis factor alpha. In vitro, in VICs isolated from AVs, Gal‐3 induced expression of inflammatory, fibrotic, and osteogenic markers through the extracellular signal‐regulated kinase 1 and 2 pathway. Gal‐3 expression was blocked in VICs undergoing osteoblastic differentiation using its pharmacological inhibitor, modified citrus pectin, or the clustered regularly interspaced short palindromic repeats/Cas9 knockout system. Gal‐3 blockade and knockdown decreased the expression of inflammatory, fibrotic, and osteogenic markers in differentiated VICs. ConclusionsGal‐3, which is overexpressed in AVs from AS patients, appears to play a central role in calcification in AS. Gal‐3 could be a new therapeutic approach to delay the progression of AV calcification in AS.